Quality assessment of mixed fruit squash: physico-chemical analysis, sensory evaluation and storage studies (Journal of the Bangladesh Agricultural University, 2014)
Fruits and vegetables belong to an essential class of foods that supply human diet with nutritive requirements including vitamins and minerals which are essential for normal body health and function. The study was carried out to determine the physico-chemical analysis and sensory qualities of mixed fruit squash. Carrot (Drocus carota), papaya (Carica papaya) and banana (Musa sapientum) juice were standardized to produce mixed squash which was stored for 9 weeks in sterilized glass bottles at room temperature. Marginal changes in pH, total soluble solids, acidity and vitamin C were observed. Estimation of vitamin C content (6.32 15.45 mg) of mixed squash showed high improvement in nutritional value of papaya juice incorporated with carrot and banana juice in squash. TSS (40.0 to 41.6) increased with gradual passage of storage time, which might be due to hydrolysis of polysaccharides into monosaccharide and oligosaccharides. The titratable acidity (1.25% to 2.97%) increased and pH (5.01 to 3.87) decreased progressively during the storage period might be due to the excessive fermentation and presence of lactic acid reducing micro- organism. The mean overall acceptability scores of more than 8 for mixed squash prepared up to 40% carrot juice incorporation with 40% papaya and 20% banana juice indicated the commercial scope for manufacturing good and nutritious squash from carrot, papaya and banana juice. However, the shelf life of mixed squash was established within 8 weeks. The product is recommended for children, youth and elderly persons to be used within 8 weeks. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21412 J. Bangladesh Agril. Univ. 12(1): 195-201, June 2014